Penerapan Prinsip-Prinsip Model Pembelajaran Kolaboratif dalam Pembelajaran BIPA: Suatu Tinjauan Literatur - Luisa, Adellia; Rangkuty, Amelia Nurul Oktaviani; Sitompul, Ayu Wardani; Harahap, Safinatul Hasanah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to conduct a literature review on the application of collaborative learning model principles in teaching Indonesian as a Foreign Language (BIPA). Collaborative learning models have become increasingly popular approaches in today's educational context, as they promote active participation, social interaction, and group-based learning. In the context of BIPA teaching, the application of collaborative learning models is crucial to facilitate effective learning for students studying Indonesian as a second language. In this literature review, we identify the main principles of collaborative learning models and analyze how these principles can be applied in the context of BIPA teaching. This literature review also explores previous studies that have investigated the application of collaborative learning models in BIPA teaching and evaluated their impact on student learning achievement. The findings of this literature review are expected to provide better insights into the potential and challenges of implementing collaborative learning models in BIPA teaching and provide guidance for further research in this field.